2019
DOI: 10.3390/polym11050843
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of EVOH-Based Amphoteric Ion Exchange Membrane Using Radiation Grafting Technique: A Preliminary Investigation on Its Application for Vanadium Redox Flow Battery

Abstract: A novel amphoteric ion exchange membrane (AIEM) was successfully prepared by one-step radiation grafting of sodium styrene sulfonate (SSS) and dimethylaminoethyl methacrylate (DMAEMA) onto ethylene-vinylalcohol copolymer (EVOH) powder and sequent transferring into film by casting method. Fourier transform infrared spectrometry (FT-IR), thermal gravimetric analyzer (TGA) and elemental analysis testified SSS and DMAEMA were successfully grafted onto EVOH. The ion exchange capacity, water uptake and proton conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Based on Figure 12 , it can be observed that M1 has the lowest IEC value of 0.291 meq/g; then the value surged to 0.635 meq/g for M2 and was followed by a steady increment in the IEC for the following membranes M3 (0.671 meq/g), M4 (0.709 meq/g), M5 (0.757 meq/g) and M6 (0.780 meq/g). The trend shows the relationship between the carrier content and IEC of the membrane, where the IEC increases in alliance with the carrier content of the membrane [ 72 ]. This is because the PIM with a higher percentage of carriers has more vacant ion-exchange sites available for the formation of carrier complexes between the carriers B 2 EHP and MG ions (Equation (9)).…”
Section: Resultsmentioning
confidence: 99%
“…Based on Figure 12 , it can be observed that M1 has the lowest IEC value of 0.291 meq/g; then the value surged to 0.635 meq/g for M2 and was followed by a steady increment in the IEC for the following membranes M3 (0.671 meq/g), M4 (0.709 meq/g), M5 (0.757 meq/g) and M6 (0.780 meq/g). The trend shows the relationship between the carrier content and IEC of the membrane, where the IEC increases in alliance with the carrier content of the membrane [ 72 ]. This is because the PIM with a higher percentage of carriers has more vacant ion-exchange sites available for the formation of carrier complexes between the carriers B 2 EHP and MG ions (Equation (9)).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to P1 , P2 presented higher thermostability within 30−240 °C (Figure S5), related to extra COOH functionalities and excessive hydrogen bonding, substantiated by the broad bands in Fourier transform infrared/FTIR spectroscopy (Figure S3). Moreover, within 250−300°C, the higher weight loss of P1 than P2 was related to the complete removals of DMAEMA moieties in P1 at 350 ο C. [ 49 ] In P2 , C(O)OH and C(O)O − functionalities degraded within 360−440 ο C. In P1 and P2 , the weight losses within 200–323 °C was related to loss of C(O)NHCH 2 OH in NMA by dehydration and deformylation forming thermostable CN functionalities, which cyclized at higher temperatures (Figure S5). [ 50,51 ] The other reason was methylene bridge formation by the self‐condensation of methylol groups of NMA moieties.…”
Section: Terpolymer Ex Situ Monomers X1a) [Mol] X2b) [Mol] X3c) [Mmolmentioning
confidence: 99%
“…As the grafting yield was increased, the conductivity rose from 3.4 to 40.0 mS/ cm and 7.4 to 114 mS/cm for the EVOH 30 and PVDF 31 membranes, respectively, following a similar trend in WU; however, vanadium crossover also was increased. 35,36 Although the grafting reactions led to high-performance membranes from low-cost starting materials, the modified membranes did not necessarily outperform benchmark materials. 35,36 Nanoparticle inclusion is another method to enhance WU, and as an example, the addition of Nd 2 Zr 2 O 7 nanotubes to a PFSA matrix increased conductivity from 59.4 mS/cm for the pure PFSA membrane to 78.9 mS/cm for a composite membrane with 1 wt % nanotubes.…”
Section: ■ Conductivitymentioning
confidence: 99%